2021
DOI: 10.3389/fonc.2021.691317
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation Network and Clinical Significance of Circular RNAs in Breast Cancer

Abstract: Breast cancer is one of the most common malignant tumors in women worldwide. Circular RNA (circRNA) is a class of structurally stable non-coding RNA with a covalently closed circular structure. In recent years, with the development of high-throughput RNA sequencing, many circRNAs have been discovered and have proven to be clinically significant in the development and progression of breast cancer. Importantly, several regulators of circRNA biogenesis have been discovered. Here, we systematically summarize recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 178 publications
(107 reference statements)
0
1
0
Order By: Relevance
“…Most studies have proven that circRNAs act as sponges of microRNAs (miRNAs) to further regulate the development of multiple human diseases [ 8 , 12 16 ]. In human BC, many circRNAs have been discovered and proven to be related to the development of BC [ 17 ]. Notably, a meta-analysis indicated that circRNAs have diagnostic value and may be potential diagnostic biomarkers for BC [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have proven that circRNAs act as sponges of microRNAs (miRNAs) to further regulate the development of multiple human diseases [ 8 , 12 16 ]. In human BC, many circRNAs have been discovered and proven to be related to the development of BC [ 17 ]. Notably, a meta-analysis indicated that circRNAs have diagnostic value and may be potential diagnostic biomarkers for BC [ 18 ].…”
Section: Introductionmentioning
confidence: 99%